Aortouni-iliac Endografting as an Alternative Salvage Procedure to Open Conversion in Failed Endovascular Aneurysm Repair. (February 2014) - Prusa, Alexander M.; Wibmer, Andreas G.; Nolz, Richard; Schoder, Maria; Lammer, Johannes; Polterauer, Peter; Kretschmer, Georg; Teufelsbauer, Harald
Purpose: To present a single-center experience with failed EVAR requiring conversions comparing open surgery to a minimally invasive procedure modifying the existing stent-graft into an aortouni-iliac (AUI) configuration. Methods: A prospectively maintained database at our tertiary care university hospital was interrogated to identify all patients with failed EVAR who had undergone either stent-graft modification into an AUI configuration or open conversion between March 1995 and January 2012. Patients with late aneurysm ruptures were excluded. The search found 30 patients (one had initial treatment elsewhere) who required conversion among the 688 patients who had undergone EVAR in that time period. Before conversion, 16 (53%) patients had prior endovascular corrections to maintain aneurysm exclusion. Results: An average time of 52.2 months (median 46.9, IQR 0.0–92.5) elapsed between initial EVAR and conversion. There were 11 early conversions (including 7 on-table), while 19 procedures were done <30 days post EVAR. Twenty-two (73%) patients underwent AUI endografting, while open conversions were carried out in 8 (27%). Mean hospital stay after conversion was 19.5 days (median 13.0, IQR 8.0–17.0). Overall mortality after conversion was 3.3% (1 patient after on-table open conversion), but since the introduction of AUI endografting as an alternative treatment approach, 30-day mortality following conversions fell to zero. Conclusion: Modification of a failed stent-graft into an AUI configuration serves as a less invasive treatment option compared to open conversion and allows salvage of the failed device. With the implementation of this alternative approach, mortality after conversion parallels the mortality of elective abdominal aneurysm repair.